Detección de Escherichia coli y salmonella spp en carne de res distribuida en diferentes expendios del municipio de Piendamó, Cauca - Fernández Sánchez, Dubar Alexander; Ordóñez Gómez, Luisa Valeria (Universidad Antonio Nariño, 2022)
The meat of res has stood out as a source of infectious or toxic diseases transmitted by food, considered a priority of public health. Therefore, it is important to establish reliable data that show the risk for health associated with the consumption of pathogenic bacteria from foods of meat origin. In this way, the purpose of this study is to determine the frequency of Escherichia Coli and Salmonella spp in meat from res, distributed on different expenses in the municipality of Piendamó, Cauca. To achieve this objective, a descriptive cross-sectional study was carried out. 30 samples of res meat were taken in different supplies dedicated to the commercialization of res meat in the municipality of Piendamó, used to analyze the prueba Agar MacConkey. The results were analyzed with the SPSS 15.0 statistical package. The bacteriological study identified that 20% (N=6) of the collected samples presented Escherichia coli and the presence of Salmonella spp. From the positive results, the report revealed that within 72 hours of incubation E. coli was isolated in the enterohemorrhagic and no other enteropathogenic germ. All strains were reported to be resistant to Ampicillin, Cephalotin, Cefuroxime, Cefoxitin, Ampicillin / sulbactam. It is concluded that the frequency of Escherichia coli in meat expenses in the municipality of Piendamó is high, 1 out of every 5 establishments contains contaminated meat.